"Stylistic Displacement" in the poem "Vito on the Nun alniswa" for "Sua'ad AL Sabah - Abu Hedba, Mohammed Sami (Journal of Humanities & Social Sciences, 2018)
This research which is titled "Stylistic of Displacement" in the poem "Vito on the Nun Alniswa" for "Sua'ad AL Sabah" tries to count the displacements that appear in the poem in its both levels the meaningful and structural sides and shows its beauty and shows its beauty and the cleary affect in the poet language and her creativity.This research which is titled "Stylistic of Displacement" in the poem "Vito on the Nun Alniswa" for "Sua'ad AL Sabah" tries to count the displacements that appear in the poem in its both levels the meaningful and structural sides and shows its beauty and shows its beauty and the cleary affect in the poet language and her creativity.In addition to that, this study tries to show the importance of stylistic of displacement in fixing the texts and discovering the artistic values and the beauty values through text language. This study discussed many theoretical issues related to Stylistic of Displacement. At beginning it had the concept of displacement in Symantec and language. Also it had the importance of beauty of stylistic of displacement, which considered by most of stylistic scholars as an important feature of the language of the poet; especially the modern poet which is considered as displacement from the ancient Arabic poetry.Then this study took in its second part on the practical side on the poet text Sua'ad ALsabah by the titled "Vito on the Nun alniswa"
Keywords: stylistic displacement; displacement; deviation; Substitutional displacement; structural displacement